Global Molecular Response of Paracoccidioides brasiliensis to Zinc Deprivation: Analyses at Transcript, Protein and MicroRNA Levels - Lorena Alves Mesquita; Alexandre Melo Bailão; Juliana Santana de Curcio; Kassyo Lobato Potenciano da Silva; Gabriel da Rocha Fernandes; Mirelle Garcia Silva-Bailão; Evandro Novaes; Célia Maria de Almeida Soares (Journal of Fungi, 2023)
Zinc is one of the main micronutrients for all organisms. One of the defense mechanisms used by the host includes the sequestration of metals used in fungal metabolism, such as iron and zinc. There are several mechanisms that maintain the balance in the intracellular zinc supply. MicroRNAs are effector molecules of responses between the pathogen and host, favoring or preventing infection in many microorganisms. Fungi of the Paracoccidioides genus are thermodimorphic and the etiological agents of paracoccidioidomycosis (PCM). In the current pandemic scenario world mycosis studies continue to be highly important since a significant number of patients with COVID-19 developed systemic mycoses, co-infections that complicated their clinical condition. The objective was to identify transcriptomic and proteomic adaptations in Paracoccidioides brasiliensis during zinc deprivation. Nineteen microRNAs were identified, three of which were differentially regulated. Target genes regulated by those microRNAs are elements of zinc homeostasis such as ZRT1, ZRT3 and COT1 transporters. Transcription factors that have zinc in their structure are also targets of those miRNAs. Transcriptional and proteomic data suggest that P. brasiliensis undergoes metabolic remodeling to survive zinc deprivation and that miRNAs may be part of the regulatory process.